An observational study to evaluate and compare the role of bilateral internal iliac artery ligation with uterine compression sutures for arresting postpartum haemorrhage in a tertiary care hospital in West Bengal - Das, Rumpa; Sarkar, Malay; Halder, Palas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Postpartum haemorrhage is the most important cause of maternal mortality which is near about 13% in developed countries and 34% in developing countries. When postpartum haemorrhage is not controlled even after aggressive medical management, immediate surgical intervention is needed which includes bilateral internal iliac artery ligation, B-Lynch compression sutures, hysterectomy as a last resort. Bilateral internal iliac artery ligation is much quicker and having lesser risk of uterine necrosis as compare to B-Lynch suture. That’s why a study was conducted to evaluate and compare the role of bilateral internal iliac artery ligation with B-Lynch compression sutures. Methods: A prospective observational study was conducted in the department of obstetrics and gynaecology in Burdwan medical college and hospital for a period of 3 years from 1st July 2019 to 30th June 2022. Out of total 62 cases of intractable postpartum haemorrhage, 31 cases underwent bilateral internal iliac artery ligation (group A) and another 31 cases underwent B-Lynch compression sutures (group B). Results: In this study, most of the women were in the age group of 21-30 years. both in group A and group B. Risk factors for postpartum haemorrhage in both groups were pre-eclampsia, abruption, placenta previa, nonprogress of labour, multiple pregnancy. Blood products requirements were much more in group B than group A. Hysterectomy needed in 12.9% cases of group A and 29.03% cases of group B. In terms of maternal outcome, out of total maternal death, 37.5% cases were under group A, 62.5% cases were under group B. Conclusions: In our study, need for hysterectomy was less in cases of bilateral internal iliac artery ligation compared with B-Lynch compression sutures. So, bilateral internal iliac artery ligation should be early resort to prevent hysterectomy in cases of atonic postpartum haemorrhage with low parity. As bilateral internal iliac artery ligation is a life saving procedure, every obstetrician must be able to perform it and should have proper knowledge of retroperitoneal anatomy to avoid injury of iliac veins and ureter.